Pengaruh Financial Literacy Terhadap Keberlangsungan Usaha (Business Sustainability) Pada UMKM Desa Jatisari - Rochmi Widayanti; Ratna Damayanti; Fithria Marwanti (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
The SMEs sector is one of the drivers of the economy, but in its development there are still many unresolved problems, one related to finance. The purpose of this research is to know the influence of financial literacy or financial knowledge owned by the SMEs businessman (manager) towards the sustainability of their business from the SMEs in the village of Jatisasri. This research is a quantitative research, using simple lineir regression to test the hypothesis and take the popolation as well as the sample of research is the businessman (manager) of SMEs in the village of Jatisari Wonogiri a number of 38 respondents. Independent variables in this research are financial literacy and business sustainability is dependent variable. The results showed that financial literacy gives effect to business sustainability of 28.9%. This shows that financial literacy or financial knowledge owned by the SMEs businessman (manager) in Jatisari is important in supporting the sustainability of their business.